Adolescent Parenting from the Perspectives of Minangkabau Customary Law and Islamic Law in the Manuscript Pedoman Hidup di Alam Minangkabau by Sulaiman Arrasuli - Dertha Mukhtar; Nunu Burhanuddin; Hayati Hayati; Dini Rizki Amalia (The Future of Education Journal, 2026)
Adolescent parenting in Minangkabau society cannot be separated from the close relationship between customary law (adat) and Islamic law (syara'). This article examines the concept of adolescent parenting based on the manuscript Pedoman Hidup di Alam Minangkabau by Sulaiman Arrasuli, with a particular focus on the integration of customary and Islamic values in family education. The study employed a library research method using a philological and descriptive qualitative approach. Data were collected from the manuscript, reputable journal articles, and previous studies on family education in Minangkabau society. The findings indicate that Sulaiman Arrasuli's concept of parenting emphasizes the development of moral character (akhlaq), respect for Minangkabau customary values, Islamic religious education, and adolescents' social responsibility within the community. Parenting is carried out through exemplary conduct, moral guidance, and collective supervision by both the family and the customary community. These values remain highly relevant in addressing the challenges of modernization and the contemporary crisis of adolescent morality.